Photoelectric conversion unit

By using a hole transport layer composed of a p-type metal oxide semiconductor layer and a specific compound in a perovskite solar cell, the problems of low photoelectric conversion efficiency and insufficient material durability in the prior art are solved, and high efficiency and Durable photoelectric conversion effect.

CN119487998APending Publication Date: 2025-02-18ANENKODO TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202380049126.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-12-28
Filing Date
2023-12-28
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The photoelectric conversion efficiency of the existing perovskite solar cells is not high, the characteristics of the hole transport layer need to be improved, and the heat resistance and durability of the existing hole transport materials are insufficient.

Method used

A hole transport layer consisting of a p-type metal oxide semiconductor layer and a hole transport material layer, which contains a compound represented by a specific chemical formula and is chemically bonded or hydrogen bonded to the p-type metal oxide semiconductor layer. , forming a single molecular layer.

Benefits of technology

It achieves excellent photoelectric conversion characteristics and durability improvement, and improves the overall performance of solar cells.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487998A_ABST
    Figure CN119487998A_ABST
Patent Text Reader

Abstract

The purpose of the present invention is to provide a photoelectric conversion cell which exhibits excellent photoelectric conversion characteristics and has improved durability. A photoelectric conversion unit (10) according to one embodiment of the present invention has a structure in which a first electrode (12), a hole transport layer (13), a photoelectric conversion layer (14), an electron transport layer (15), and a second electrode (16) are stacked in this order. The photoelectric conversion layer (14) contains a perovskite compound. The hole transport layer (13) includes a p-type metal oxide semiconductor layer (13-1) and a hole transport material layer (13-2). The hole transport material layer (13-2) contains a compound represented by the following chemical formula (I): Ar1-(L1-X1) n (I) in which Ar1 is a structure containing an aromatic ring and may contain a heteroatom among the atoms constituting the aromatic ring, and Ar1 may have a substituent other than-L1-X1. And n is an integer of 1 or more, and when n is 2 or more, the structures represented by-L1-X1 may be the same as or different from each other. L1 is a divalent linking group or a single bond that bonds Ar1 and X1. X1 is a group capable of chemically bonding or hydrogen bonding with a p-type metal oxide semiconductor.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a photoelectric conversion unit. Background Art

[0002] In recent years, solar power generation has attracted much attention as a clean energy source, and the development of solar cells has also been continuously promoted. As one of them, solar cells using perovskite materials for light absorption layers are rapidly attracting people's attention as new next-generation solar cells that can be manufactured at low cost. For example, a solution-type solar cell using perovskite materials for light absorption layers is reported in non-patent document 1. In addition, a solid-state perovskite solar cell showing high efficiency is also reported in non-patent document 2.

[0003] As the basic structure of perovskite solar cells, there are known forward structures: an electron transport layer, a light absorption layer (perovskite layer), a hole transport layer (also called a vacancy transport layer), and a back electrode are stacked in this order on the electrode; a reverse structure: a hole transport layer, a light absorption layer, an electron transport layer, and a back electrode are stacked in this order on the electrode. An electron transport layer composed of a porous shape is provided between the electron transport layer and the perovskite layer. Among them, the hole transport layer generally uses a hole transport material of an organic semiconductor (for example, non-patent documents 3 to 10). Prior art literature Non-patent literature

[0004] Non-patent document 1: Journal of the American Chemical Society, 2009, 131, 6050-6051. Non-patent document 2: Science, 2012, 388, 643-647. Non-patent document 3: ACS Appl. Mater. Interfaces, 2017, 9, 24778-24787. Non-patent document 4: Energy Environ. Sci., 2014, 7, 1454-1460. Non-patent document 5: J. Mater. Chem. A, 2014, 2, 6305-6309. Non-patent document 6: J. Mater. Chem. A, 2015, 3, 12139-12144. Non-patent literature 7: J. Mater. Chem. A, 2018, 6, 7950-7958. Non-patent document 8: ACS Appl. Mater. Interfaces, 2015, 7, 11107-11116. Non-patent document 9: Energy & Environmental Science 2014, 7, 2963-2967. Non-patent literature 10: Adv. Energy Mater., 2018, 8, 1801892. Summary of the invention Technical problem to be solved by the invention

[0005] However, the photoelectric conversion efficiency of existing perovskite solar cells cannot be said to be sufficient. In order to improve the photoelectric conversion efficiency of solar cells, it is particularly important to improve the characteristics of the hole transport layer. As the hole transport material used for the hole transport layer, for example, trimerized indene compounds (non-patent document 3), diketopyrrolopyrrole compounds (non-patent document 4), thiophene compounds (non-patent documents 5, 6), dithienopyrrole (non-patent document 7), etc. have been reported so far. However, there is almost no report of such a compound: it can play a useful degree of photoelectric conversion efficiency as a perovskite solar cell. Therefore, it is proposed to develop Spiro-OMeTAD ([2,2',7,7'-tetrakis (N, N-di-(4-methoxyphenyl)amino)-9,9'-spirobifluorene]) as a hole transport material for dye-sensitized solar cells, but it is known that its heat resistance is low (non-patent document 8). In addition, it is known that a polymer material having a triphenylamine skeleton, called PTAA (poly[bis(4-phenyl)(2,4,6-trimethylphenyl)amine]), also has low light resistance. Furthermore, when these materials are used as hole transport materials for the p-buffer layer, it is necessary to add LiTFSI salt (lithium bis(trifluoromethylsulfonyl)imide) as an additive to improve conductivity, which is considered to be one of the causes of element degradation (non-patent document 9). In addition, a carbazole-type hole transport material having phosphonic acid has been reported in recent years (non-patent document 10). This compound reacts with an indium tin compound (ITO) used as a transparent electrode and forms a monomolecular layer on the transparent electrode. It is reported that the photoelectric conversion efficiency of the hole transport compound forming this monomolecular layer exceeds 20%, which is a very excellent compound, but when the coverage of the hole transport layer on the electrode is insufficient, there is a case where the electrode contacts the photoelectric conversion layer, resulting in a decrease in photoelectric conversion characteristics and insufficient durability.

[0006] Therefore, an object of the present invention is to provide a photoelectric conversion unit that exhibits excellent photoelectric conversion characteristics and has improved durability. Technical means of solving problems

[0007] One embodiment of the present invention is a photoelectric conversion unit. The photoelectric conversion unit is a photoelectric conversion unit in which a first electrode, a hole transport layer, a photoelectric conversion layer, an electron transport layer, and a second electrode are stacked in this order. The photoelectric conversion layer comprises a perovskite compound; The hole transport layer includes a p-type metal oxide semiconductor layer and a hole transport material layer, the p-type metal oxide semiconductor layer is stacked on the main surface of the first electrode on one side of the photoelectric conversion layer, the hole transport material layer is stacked on the main surface of the p-type metal oxide semiconductor layer on one side of the photoelectric conversion layer, and contains a compound represented by the following chemical formula (I). Ar 1 -(L 1 -X 1 )n...(I) In the chemical formula (I), Ar 1 It is a structure containing an aromatic ring, and the atoms constituting the aromatic ring may contain heteroatoms. 1 Can have -L 1 -X 1 n is an integer greater than 1, and when n is greater than 2, -L 1 -X 1 The structures represented may be the same or different. 1 is bonded to Ar 1 and X 1 A divalent connecting group or a single bond. 1 It is a group that can chemically bond or hydrogen bond with the p-type metal oxide semiconductor. In the photoelectric conversion unit of the above embodiment, the hole transport material layer may include a compound represented by the following chemical formula (II). A 1 -L 2 -X 2 . ..(II) A 1 is an atomic group containing at least one substituent or structure selected from the group consisting of an alkoxy group, a hydroxyl group, a carboxyl group, a dihydroxyphosphonyl group, a dialkylphosphonyl group, a hydroxysulfonyl group, an amino group, a monoalkylamino group, a dialkylamino group, a monoarylamino group, a diarylamino group, a monoalkylaminocarbonyl group, a dialkylaminocarbonyl group, an alkylcarbonyloxy group, an alkoxycarbonyl group, an aminocarbonyl group, an aminocarbonylamino group, an alkylcarbonylamino group, an alkylsulfonylamino group, an aminosulfonyl group, and a nitrogen-containing heterocyclic group. 2 It is bonded A 1 and X 2 A divalent connecting group or a single bond. 2 The group is capable of chemically bonding or hydrogen bonding with the first electrode. The compound represented by the chemical formula (I) may form a monomolecular layer. The molar ratio of the compound represented by the chemical formula (II) to the compound represented by the chemical formula (I) may be 1:100 to 1:1. X in the chemical formula (I) 1 They can be selected from: dihydroxyphosphonyl (-P=O(OH)2), carboxyl (-COOH), sulfonyl (-SO3H), boric acid (-B(OH)2), trihalosilyl (-SiX3, but X is a halogen group), trialkoxysilyl (-Si(OR)3, but R is an alkyl group), trihydroxysilyl, and dialkylphosphonyl. X in the chemical formula (II) 1 They can be selected from: dihydroxyphosphonyl (-P=O(OH)2), carboxyl (-COOH), sulfonyl (-SO3H), boric acid (-B(OH)2), trihalosilyl (-SiX3, but X is a halogen group), trialkoxysilyl (-Si(OR)3, but R is an alkyl group), trihydroxysilyl, and dialkylphosphonyl. The perovskite compound may be an organic-inorganic perovskite compound. The perovskite compound may contain at least one of tin or lead. The organic-inorganic perovskite compound may contain at least one of tin or lead. At least part of the compounds represented by the chemical formula (I) may form acid addition salts. At least part of the compounds represented by the chemical formula (II) may form acid addition salts. The p-type metal oxide semiconductor layer may be formed of p-type metal oxide semiconductor particles. The diameter of the p-type metal oxide semiconductor particles may be 1.0 to 30.0 nm. Effects of the Invention

[0008] According to the present invention, a photoelectric conversion unit which exhibits excellent photoelectric conversion characteristics and has improved durability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS

[0009] Figure 1 It is a cross-sectional view showing an example of the structure of a photoelectric conversion unit according to an embodiment. Figure 2 It is a graph showing the particle size distribution of nickel oxide powder. DETAILED DESCRIPTION

[0010] The present invention will be further described in detail by giving examples. However, the present invention is not limited to the following description. It should be noted that the following description is based on the case where the photoelectric conversion unit of the embodiment is a solar cell.

[0011] [Photoelectric conversion unit] Figure 1 1 is a cross-sectional view showing an example of the structure of the photoelectric conversion unit 10 according to the embodiment. It should be noted that for the sake of convenience of explanation, appropriate omissions, enlargements, etc. are performed to schematically illustrate the structure of the photoelectric conversion unit 10. Figure 1 .like Figure 1 As shown, the photoelectric conversion unit 10 has a stacked structure, and a first electrode 12, a hole transport layer 13, a photoelectric conversion layer 14, an electron transport layer 15 and a second electrode 16 are stacked in this order on a support (also called a substrate, base material, etc.) 11. Hereinafter, each structure of the photoelectric conversion unit 10 will be described in detail.

[0012] [Support] The support 11 is not particularly limited, and for example, a substrate that can be used for a photoelectric conversion unit of a general solar cell or the like can be appropriately used. As the substrate, for example, glass, a plastic plate, a plastic film, an inorganic crystal, etc. can be cited. In addition, a substrate having at least one of a metal film, a semiconductor film, a conductive film, and an insulating film formed on a part or all of the surface of these substrates can also be appropriately used as the support 11. The size, thickness, etc. of the support 11 are also not particularly limited, and for example, can be the same as or based on the photoelectric conversion unit of a general solar cell or the like.

[0013] [First electrode] The first electrode 12 is, for example, a layer having a function of supporting the hole transport layer 13 and extracting holes from the photoelectric conversion layer 14. In addition, the first electrode 12 is, for example, a layer functioning as an anode (positive electrode).

[0014] For example, the first electrode 12 can be formed directly on the support 11. For example, the first electrode 12 can be a transparent electrode formed by a conductor. As the transparent electrode, although not particularly limited, for example, it can be listed: tin-doped indium oxide (ITO) film, impurity-doped indium oxide (In2O3) film, impurity-doped zinc oxide (ZnO) film, fluorine-doped tin dioxide (FTO) film, a laminated film formed by laminating two or more of these films, gold, silver, copper, aluminum, tungsten, titanium, chromium, nickel and cobalt, etc. These are single or mixed in two or more, and can be a single layer or a laminate. In addition, these films can also realize functions such as diffusion prevention layers. Although the thickness of the first electrode 12 is not particularly limited, for example, it is preferred to adjust the film resistance to 5 to 15Ω / □ (per unit area). The method for forming the first electrode 12 is not particularly limited, but for example, it can be obtained by a known film forming method according to the material to be formed. In addition, the shape of the first electrode 12 is not particularly limited, but for example, it can be a film or a grid such as a mesh. The method for forming the first electrode 12 on the support 11 is not particularly limited, and for example, it can be a known method, preferably vacuum film forming such as vacuum evaporation and sputtering. In addition, the first electrode 12 can use a patterned material. As a patterning method, for example, a method of laser or immersion in an etching solution, a method of patterning using a mask during vacuum film forming, etc. are listed, but it is not limited to these two methods, and any method can be used in the present invention. In addition, for the purpose of reducing the resistance value, the first electrode 12 can be used in combination with metal wiring, etc. There is no particular limitation on the material of the metal wiring (metal lead), but for example, aluminum, copper, silver, gold, platinum, nickel, etc. are listed. The metal lead is formed on the first substrate by, for example, evaporation, sputtering, crimping, etc., and an ITO layer and an FTO layer are provided thereon, or a metal lead is provided on ITO and FTO, so that it can be used in combination.

[0015] [Hole Transport Layer] like Figure 1 As shown, the hole transport layer 13 includes a p-type metal oxide semiconductor layer 13 - 1 and a hole transport material layer 13 - 2 .

[0016] The p-type metal oxide semiconductor layer 13 - 1 is stacked on the main surface of the first electrode 12 on the photoelectric conversion layer 14 side.

[0017] The p-type metal oxide semiconductor used for the p-type metal oxide semiconductor layer 13-1 is preferably a semiconductor material formed of a metal oxide that transports holes. Specifically, single or mixed oxides formed of oxides of nickel, copper, aluminum, etc. are listed. The p-type metal oxide semiconductor layer 13-1 can be a single layer or a multilayer. In the case of a multilayer, it can be a porous shape in which semiconductor particles of different particle sizes are coated in multiple layers. In the case of a porous shape, the particle size of the semiconductor particles is preferably 3 to 100 nm, and more preferably 5 to 70 nm. The film thickness of the p-type metal oxide semiconductor layer 13-1 is preferably 1 to 1000 nm, and more preferably 10 to 500 nm. The method for forming the p-type metal oxide semiconductor layer 13-1 is not particularly limited, and can be any of vacuum film formation such as sputtering or ion plating or wet film formation such as sol-gel. The p-type metal oxide semiconductor layer 13 - 1 may be formed of p-type metal oxide semiconductor particles. In this case, the diameter of the particles is, for example, 0.2 to 60.0 nm, preferably 1.0 to 30.0 nm, more preferably 1.0 to 10.0 nm, and further preferably 2.0 to 3.5 nm. The diameter of the p-type metal oxide semiconductor particles mentioned here refers to the average particle size (particle size with a cumulative value of 50%) measured by a dynamic scattering method using a zeta potential, particle size, and molecular weight measurement system ELSZ-2000 manufactured by Otsuka Electronics, after the particles are fully dispersed in deionized water at room temperature and the resulting dispersion is passed through a 0.45 μm PVDF filter. The diameter of the p-type metal oxide semiconductor particles used to form the p-type metal oxide semiconductor layer (a layer formed using p-type metal oxide semiconductor particles) can be obtained by the above-mentioned measurement method. Alternatively, the diameter can be obtained by taking out the particles contained in the p-type metal oxide semiconductor layer (a layer formed using p-type metal oxide semiconductor particles) in the completed photoelectric conversion unit and measuring them by the above-mentioned measurement method. It should be noted that, when the p-type metal oxide semiconductor layer 13-1 is formed by p-type metal oxide semiconductor particles, at least a portion of all p-type metal oxide semiconductors in the p-type metal oxide semiconductor layer 13-1 can be formed by p-type metal oxide semiconductor particles. For example, preferably 30 to 100 mass % (preferably 70 to 100 mass %, more preferably 90 to 100 mass %, and further preferably 98 to 100 mass %) of the total mass of the p-type metal oxide semiconductors in the p-type metal oxide semiconductor layer 13-1 is formed by p-type metal oxide semiconductor particles.

[0018] As long as the hole transport performance is not impaired, the surface of the p-type metal oxide semiconductor layer 13-1 may also be covered with a very thin insulating layer. As the insulating layer, there can be listed: a single or mixed insulating metal oxide formed by oxides of aluminum, magnesium, silicon, niobium, strontium, barium, titanium, zinc, vanadium, etc. The film thickness of the insulating metal oxide is preferably thin, preferably 1 to 20 nm, and more preferably 2 to 10 nm. The method for forming the insulating metal oxide is not particularly limited, and it can be any of vacuum film formation by sputtering or ion plating or wet film formation by sol-gel.

[0019] The hole transport material layer 13-2 is formed on the main surface of the p-type metal oxide semiconductor layer 13-1 on the side of the photoelectric conversion layer 14. The hole transport material layer 13-2 contains a compound represented by the following chemical formula (I). In other words, the hole transport material layer 13-2 covers the main surface of the p-type metal oxide semiconductor layer 13-1 on the side of the photoelectric conversion layer 14. A preferred embodiment of the hole transport material layer 13-2 contains a compound represented by the following chemical formula (I), which is chemically bonded or hydrogen-bonded to the p-type metal oxide semiconductor constituting the p-type metal oxide semiconductor layer 13-1. Ar 1 -(L 1 -X 1 )n...(I) In the chemical formula (I), Ar 1 It is a structure containing an aromatic ring, and the atoms constituting the aromatic ring may contain heteroatoms, Ar 1 Can have -L 1 -X 1 n is an integer greater than 1, and when n is greater than 2, -L 1 -X 1 The structures represented may be the same or different from each other. The upper limit of n is preferably 3 or 4. 1 is bonded to Ar 1 and X 1 A divalent connecting group or a single bond. 1 It is a group that can chemically bond or hydrogen bond with the p-type metal oxide semiconductor.

[0020] (Compound represented by chemical formula (I)) In the chemical formula (I), X 1 Each is independently selected from: dihydroxyphosphonyl (-P=O(OH)2), carboxyl (-CO OH), sulfonyl (-SO3H), boric acid (-B(OH)2), trihalosilyl (-SiX3, but X is a halogen group), trialkoxysilyl (-Si(OR)3, but R is an alkyl group), trihydroxysilyl, dialkylphosphonyl.

[0021] In the chemical formula (I), specifically, Ar 1 Preferred examples include an aromatic ring group, a group in which a plurality of aromatic ring groups are bonded via a single bond, and a group in which one or more aromatic ring groups are condensed into a non-aromatic ring.

[0022] The aromatic ring group may be monocyclic or polycyclic (e.g., 2 to 14 rings), and may have one or more (e.g., 1 to 10) heteroatoms (nitrogen atoms, sulfur atoms, and / or oxygen atoms). The aromatic ring group preferably has 5 to 40 ring member atoms. Examples of the aromatic ring group include a benzene ring group, a pyrrole ring group, a furan ring group, a thiophene ring group, and a group in which two or more (for example, 2 to 14) rings selected from these are condensed.

[0023] Examples of the aromatic ring groups constituting the group formed by the plurality of aromatic ring groups bonded via single bonds include the above-mentioned aromatic ring groups. The number of the aromatic ring groups bonded via single bonds is preferably 2 to 6, for example. Specific examples of the group formed by bonding a plurality of aromatic ring groups via single bonds include a biphenyl ring group and a bithiophene ring group.

[0024] Examples of the aromatic ring group constituting the group in which one or more aromatic ring groups are fused to form a ring having no aromaticity include the aromatic ring groups mentioned above. In the group formed by condensing one or more aromatic ring groups into a ring having no aromatic property, the number of aromatic ring groups condensed into a ring having no aromatic property is preferably 2 to 6, for example. In the group formed by condensing one or more aromatic ring groups into a non-aromatic ring, the non-aromatic ring may be present in only one or in a plurality. In the group formed by condensing one or more aromatic ring groups into a non-aromatic ring, the non-aromatic rings are each independent and may be a monocyclic ring or a polycyclic ring (e.g., 2 to 14 rings), and may have one or more (e.g., 1 to 10) heteroatoms (nitrogen atoms, sulfur atoms and / or oxygen atoms, etc.). Specific examples of the group in which one or more aromatic ring groups are fused to form a non-aromatic ring include a phenothiazine ring group and a 1,2:3,4:5,6:7,8-tetrakis[imino(1,2-phenylene)]cyclooctatetraene ring group.

[0025] In the chemical formula (I), L 1 is a divalent linking group, for example, *1-alkylene-*2, *1-alkylene-aromatic ring group-*2. Here, *1 represents Ar 1 The bonding position of the side, *2 indicates X1 The alkylene group may be linear or branched, and preferably has 1 to 6 carbon atoms. Examples of the aromatic ring group that can become Ar include 1 The alkylene group and the aromatic ring group may further have a substituent.

[0026] Specific examples of the compound represented by the chemical formula (I) include compounds (A-01) to (A-21) having the following structures. [Chemistry 1] [Chemistry 2] [Chemistry 3] [Chemistry 4] [Chemistry 5]

[0027] The compound represented by the chemical formula (I) may be formed as a monomolecular layer on the p-type metal oxide semiconductor layer 13 - 1 , for example.

[0028] (Compound represented by chemical formula (II)) In addition to the compound represented by the chemical formula (I) described above, the hole transport material layer 13-2 may also include a compound represented by the following chemical formula (II). In other words, the compound represented by the following chemical formula (II) is used in combination as a co-adsorbent. In a preferred embodiment of the hole transport material layer 13-2, the compound represented by the chemical formula (II) is chemically bonded or hydrogen-bonded to the p-type metal oxide semiconductor constituting the p-type metal oxide semiconductor layer 13-1. A 1 -L 2 -X 2 ...(II) A 1It may be an organic amino group such as a monoalkylamino group, a dialkylamino group, a monoarylamino group, a diarylamino group, an aminocarbonylamino group, an alkylcarbonylamino group, an alkylsulfonylamino group, or the like; an alkoxy group, a hydroxyl group, a carboxyl group, a dihydroxyphosphonyl group, a dialkylphosphonyl group, a hydroxysulfonyl group, an amino group, a monoalkylaminocarbonyl group, a dialkylaminocarbonyl group, an alkylcarbonyloxy group, an alkoxycarbonyl group, an aminocarbonyl group, an aminosulfonyl group, a nitrogen-containing heterocyclic group (which may or may not be aromatic, may be a monocyclic group or a polycyclic group, the number of the ring member atoms is preferably 5 to 15, the number of the nitrogen atoms in the ring member atoms is preferably 1 to 5, and may have heteroatoms other than nitrogen atoms (preferably 1 to 3). For example, it is an atomic group containing one or more substituents or structures, and the substituents or structures are selected from: pyridine ring group, quinoline ring group, aziridine ring group, azetidine ring group, pyrrolidine ring group, imidazolidinyl ring group, imidazolidin-2-one ring group, 2,3-dihydro-1H-pyrrole ring group, pyrrole ring group, pyrazole ring group, imidazole ring group, 1H-1,2,3-triazole ring group, 2H-1,2,3-triazole ring group, thiazole ring group, morpholine ring group, piperidine ring group, piperazine ring group, pyrazine ring group, hexamethyleneimine ring group, 1H-azacycloheptriene ring group, indole ring group, 2,3-trimethyleneindoline ring group, quinoxaline ring group). 1 It can also be the substituents or structures listed above. 1 When the substituents or structures listed above have an alkyl portion (including the alkyl portion of an alkoxy group, etc.), the alkyl group may be independently linear or branched, and preferably has 1 to 8 carbon atoms. L 2 It is bonded A 1 and X 2 A divalent connecting group or a single bond. 2 The group is capable of chemically bonding or hydrogen bonding with the first electrode.

[0029] In the compound represented by the chemical formula (II), 1 The hydrophilic function improves the wettability of the perovskite solution applied on the hole transport layer 13. By improving the wettability of the perovskite solution, the perovskite layer can be applied uniformly, so it is believed that the effect of reducing unevenness can be achieved especially when applying on a large area.

[0030] In the chemical formula (II), 1 When the atomic group represented by contains a monoarylamino group or a diarylamino group, examples of the aryl moiety in these groups include: 1 An aromatic ring group, the same group as the above group. By A 1The atomic group represented by may be an organic amino group such as a monoalkylamino group, a dialkylamino group, a monoarylamino group, a diarylamino group, an aminocarbonylamino group, an alkylcarbonylamino group, an alkylsulfonylamino group, an alkoxy group, a dialkylphosphonyl group, an amino group, a monoalkylaminocarbonyl group, a dialkylaminocarbonyl group, an alkylcarbonyloxy group, an alkoxycarbonyl group, an aminocarbonyl group, an aminosulfonyl group, or a nitrogen-containing heterocyclic group, and may further have one or more (preferably 1 to 6) substituents. The substituents that these groups may further have may be the same as X in the chemical formula (II). 2 or -L 2 -X 2 In the compound represented by the chemical formula (II), as a whole, -L in the chemical formula (II) 2 -X 2 It is preferred that there are two or more (eg, 2 to 6) groups that can be formed.

[0031] In the chemical formula (II), X 2 Each is independently selected from: dihydroxyphosphonyl (-P=O(OH)2), carboxyl (-COOH), sulfonyl (-SO3H), boric acid (-B(OH)2), trihalosilyl (-SiX3, but X is a halogen group), or trialkoxysilyl (-Si(OR)3, but R is an alkyl group), trihydroxysilyl, dialkylphosphonyl.

[0032] In the chemical formula (II), L 2 is a divalent linking group, for example, an alkylene group (which may be linear or branched, and preferably has 1 to 8 carbon atoms), vinylene, vinylene, ethynyl, an aromatic ring group (for example, as an aromatic ring group that can be Ar in the chemical formula (I) 1 The aromatic ring groups described above are aromatic ring groups), non-aromatic ring groups (which may be monocyclic or polycyclic and may have heteroatoms. For example, piperazine ring groups are listed), -O-, -S-, -NR N -(R N is a hydrogen atom or an alkyl group. The alkyl group may be linear or branched, and the number of carbon atoms is preferably 1 to 8), and a divalent linking group formed by a combination of two or more of these (e.g., 2 to 6). The divalent linking group formed by a combination of two or more of the above may be a combination of groups of the same type (however, a combination of continuous bonds between alkylene groups is not included). Where possible, these divalent linking groups may also have one or more (e.g., 1 to 6) substituents. For example, as substituents, they may have one or more (e.g., 1 to 6) A 1 or X 2 The same groups as those described above.

[0033] Specific examples of the compound represented by the chemical formula (II) include 3-methoxypropionic acid, 3-hydroxypropionic acid, 2-hydroxypropionic acid, malonic acid, succinic acid, glutaric acid, adipic acid, sebacic acid, phthalic acid, terephthalic acid, maleic acid, fumaric acid, citraconic acid, mesaconic acid, methylene succinic acid, allylmalonic acid, isopropylidene succinic acid, acetylene dicarboxylic acid, dimethyl terephthalate, diethyl terephthalate, 4-[4-(2-methyl-2-oxo-1-yl)-1-piperidin ... ,4'-biphenyldicarboxylic acid, 4,4'-biphenyldicarboxylic acid diethyl ester, 4-methoxybenzoic acid, 3,4-dimethoxybenzoic acid, 4-(methylamino)benzoic acid, 4-(methylamino)benzenesulfonic acid, 4-(methylamino)butyric acid, 3-(carboxymethylamino)propionic acid, 6-acetoxy-2-naphthoic acid, acetylsalicylic acid, 4-(methoxycarbonyl)cyclohexanecarboxylic acid, 4-(methoxycarbonyl)phenylboronic acid, 4-(N,N- diethylaminocarbonyl)phenylboronic acid, 3-(methylaminocarbonyl)acrylic acid, N-(aminocarbonyl)aspartic acid, 4-acetamidobenzoic acid, 2-(acetamido)acrylic acid, gallic acid, 4-pyridinecarboxylic acid, 6-quinolinecarboxylic acid, aspartic acid, 2,2-diethoxyethylphosphonic acid, methylenediphosphonic acid, 1,2-ethylenediphosphonic acid, 1,2-ethylenediphosphonic acid tetraethyl, 1,3-propenyldiphosphonic acid, 3, 4-dimethoxyphenylphosphonic acid, (4-hydroxybenzyl)phosphonic acid, 4-hydroxyphenylphosphonic acid, [3-(3-carboxypiperazin-1-yl)propyl]phosphonic acid, (pyridin-4-ylmethyl)phosphonic acid, (pyridin-3-ylmethyl)phosphonic acid, 4-phosphinobenzoic acid, 3-phosphinopropionic acid, 4-phosphinobutyric acid, (4-methoxybenzyl)phosphonic acid diethyl ester, p-carboxybenzenesulfonamide, 2-(dimethylamino)ethanesulfonic acid and 1,2-ethanesulfonic acid, etc.

[0034] As L 2 Specific examples include alkylene groups such as 1,1-ethylene, 1,2-ethylene, 1,3-propylene, and 2-ethyl-1,6-hexene, and a portion of the alkylene group may be an alkenylene group having a carbon-carbon double bond or an alkynylene group having a triple bond. In addition, arylene groups such as 1,2-phenylene, 1,4-phenylene, 1,5-naphthylene, and 4,4'-biphenylene, 2,5-thienylene, 5,5'-bithienylene, 2,5-thieno[3,2-b]thienylene, and 2,6-pyridylene may be listed.

[0035] In the compound represented by the above chemical formula (II), as the case where a salt is formed from a nitrogen atom and an anion, ammonium salt, aziridine salt, aziridine salt, azetidine salt, pyrrolidine salt, pyrrolidine salt, pyrazole salt, pyrrolidine salt, pyrazole salt, imidazolidinium salt, triazole salt, tetrazolium salt, piperidine salt, piperazine salt, pyridinium salt, pyrazine salt, morpholine salt, thiazole salt, azepanium salt, azepine salt, indolinium salt, indolinium salt, quinolinium salt, isoquinolinium salt, quinoxaline salt, phenanthroline salt and phenazine salt are listed. As the acid that reacts with the compound represented by the above chemical formula (II) to form a salt, any of the organic acids and inorganic acids described later as acids that form acid addition salts may be used, or a mixture thereof.

[0036] Specific examples of the compound represented by the chemical formula (II) include compounds (B-01) to (B-52) having the following structures. [Chemistry 6] [Chemistry 7] [Chemistry 8] [Chemistry 9] [Chemistry 10] [Chemistry 11]

[0037] The compound represented by the chemical formula (II) may be formed as a monomolecular layer on the p-type metal oxide semiconductor layer 13 - 1 , for example.

[0038] In the hole transport material layer 13-2, the total content of the compound represented by chemical formula (I) (however, including the above-mentioned salt form) and the compound represented by chemical formula (II) (however, including the above-mentioned salt form) is preferably 70 to 100 mass %, more preferably 90 to 100 mass %, and further preferably 99 to 100 mass %, relative to the mass of the hole transport material layer 13-2.

[0039] The molar ratio of the compound represented by chemical formula (II) (including the above-mentioned salt form) to the compound represented by chemical formula (I) (including the above-mentioned salt form) is preferably 1:100 to 1:1, more preferably 1:80 to 1:2, and further preferably 1:50 to 1:5.

[0040] (Method for Forming Hole Transport Material Layer) The method for forming the hole transport material layer 13-2 is not particularly limited. For example, the hole transport material layer 13-2 can be formed by adsorbing the compound represented by the chemical formula (I) or the compound represented by the chemical formula (I) and the chemical formula (II) on the p-type metal oxide semiconductor layer 13-1 to form a monolayer. The method for forming a monolayer by adsorbing the compound represented by the chemical formula (I) or the compound represented by the chemical formula (I) and (II) on the p-type metal oxide semiconductor layer 13-1 is not particularly limited. For example, the compound represented by the chemical formula (I) or the compound represented by the chemical formula (I) and (II) can be dissolved in a solvent to contact and bond with the p-type metal oxide semiconductor layer 13-1. The bonding between the compound represented by the chemical formula (I) and the p-type metal oxide semiconductor layer 13-1 and the bonding between the compound represented by the chemical formula (II) and the p-type metal oxide semiconductor layer 13-1 are not particularly limited and can be either a physical bond or a chemical bond. The type of the bond is not particularly limited, and may be any one of, for example, a hydrogen bond, an ester bond, and a chelate bond, etc. The solvent used to dissolve the compound represented by the chemical formula (I) and the compound represented by the chemical formula (II) is also not particularly limited, and may be, for example, one of water and an organic solvent, or both. More specifically, examples of the solvent include water, alcohols such as methanol, ethanol and 2-propanol, ethers such as diethyl ether and diisopropyl ether, ketones such as acetone and methyl isobutyl ketone, esters such as ethyl acetate, isobutyl acetate and γ-butyrolactone, heterocyclics such as tetrahydrofuran and thiophene, amides such as N,N-dimethylformamide, N,N-dimethylacetamide and N-methylpyrrolidone, sulfoxides such as dimethyl sulfoxide, sulfones such as diethyl sulfone and cyclopentane, nitriles such as acetonitrile and 3-methoxypropionitrile, aromatic compounds such as benzene, toluene and chlorobenzene, halogen solvents such as dichloromethane and chloroform, and fluorine solvents such as chlorofluorocarbons, hydrochlorofluorocarbons and hydrofluorocarbons. These solvents may be used alone or in combination of two or more.

[0041] The specific method for adsorbing the compound represented by the chemical formula (I) or the compound represented by the chemical formula (I) and (II) on the p-type metal oxide semiconductor layer 13-1 to form a monolayer is not particularly limited, and for example, known methods such as immersion method, spray method, spin coating method, and rod coating method can be listed. The temperature during adsorption is not particularly limited, but is preferably -20°C to 100°C, and more preferably 0°C to 50°C. The adsorption time is also not particularly limited, but is preferably, for example, 1 second to 48 hours, and more preferably 10 seconds to 1 hour.

[0042] In addition, after the above-mentioned adsorption treatment, for example, washing may or may not be performed. The washing method is not particularly limited, and for example, a known method can be appropriately used.

[0043] After the above-mentioned adsorption treatment or the above-mentioned washing, a heat treatment may or may not be performed. The temperature of the heat treatment is preferably 50°C to 150°C, more preferably 70°C to 120°C. The heat treatment time is preferably 1 second to 48 hours, more preferably 10 seconds to 1 hour. In addition, the heat treatment may be performed in air or in vacuum, for example.

[0044] In the present embodiment, the “substituent” is not particularly limited, but examples thereof include: alkyl, alkenyl, alkynyl, unsaturated aliphatic hydrocarbon, alkoxy, aralkyl, aryl, arylalkenyl, heteroaryl, halogen atoms (fluorine, chlorine and / or bromine atoms, etc.), hydroxyl (-OH), mercapto (-SH), alkylthio (-SR and R are alkyl), amino, sulfonyl, nitro, diazo, cyano, nitrile, trifluoromethyl, etc.

[0045] In addition, in the present embodiment, when there are isomers such as tautomers or stereoisomers (e.g., geometric isomers, conformational isomers, and optical isomers) in the compound, any isomer may be used in the present embodiment unless otherwise specified. In addition, in the present embodiment, when the compound represented by chemical formula (I) or chemical formula (II) is capable of generating a salt, the salt may also be used in the present embodiment unless otherwise specified. The salt may be an acid addition salt or a base addition salt. Furthermore, the acid generating the acid addition salt may be an inorganic acid or an organic acid; the base generating the base addition salt may be an inorganic base or an organic base. The inorganic acid is not particularly limited, but for example, sulfuric acid, phosphoric acid, hydrofluoric acid, hydrochloric acid, hydrobromic acid, hydroiodic acid, hypofluoric acid, hypochlorous acid, hypobromous acid, hypoiodous acid, fluorous acid, chlorous acid, bromous acid, iodous acid, fluoric acid, hydrochloric acid, bromic acid, iodic acid, perfluoric acid, perchloric acid, perbromic acid and periodic acid are listed. The organic acid is not particularly limited, but for example, p-toluenesulfonic acid, methanesulfonic acid, oxalic acid, p-bromobenzenesulfonic acid, carbonic acid, succinic acid, citric acid, benzoic acid and acetic acid are listed. The inorganic base is not particularly limited, but for example, ammonium hydroxide, alkali metal hydroxide, alkaline earth metal hydroxide, carbonate and bicarbonate are listed. More specifically, for example, sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, calcium hydroxide and calcium carbonate are listed. The organic base is not particularly limited, but for example, ethanolamine, triethylamine and tris(hydroxymethyl)aminomethane are listed. The preparation method of these salts is also not particularly limited, for example, they can be prepared by appropriately adding the acid or base to the compound according to a known method.

[0046] [Photoelectric conversion layer] The photoelectric conversion layer 14 is not particularly limited, and may be, for example, the same as the photoelectric conversion layer used in a photoelectric conversion unit of a general solar cell, etc. The photoelectric conversion layer 14 may include, for example, a perovskite compound. The perovskite compound may be, for example, an organic-inorganic perovskite compound represented by the following chemical formula (III). XαYβZγ...(III)

[0047] In the chemical formula (III), the ratio of α:β:γ is 3:1:1, and β and γ represent integers greater than 1. X represents a halogen ion, Y represents an organic compound having an amino group, and Z represents a metal ion. The photoelectric conversion layer 14 containing the perovskite compound is preferably arranged adjacent to the electron transport layer 15 described later. It should be noted that the ratio of α:β:γ is, for example, 3:1.05:0.95, and is not necessarily 3:1:1.

[0048] X in the chemical formula (III) is not particularly limited and can be appropriately selected depending on the purpose, and examples thereof include halogen ions such as chlorine, bromine, and iodine. These may be used alone or in combination of two or more.

[0049] As Y in the chemical formula (III), alkylamine compound ions (organic compounds having amino groups) such as methylamine, ethylamine, n-butylamine, and formamidine are listed, and not limited to organic, there are also alkali metal ions such as cesium, potassium, and rubidium. Alkylamine compound ions and alkali metal ions can be used alone or in combination of two or more. In addition, organic (alkylamine compound ions) and inorganic (alkali metal ions) can be used in combination, for example, cesium ions and formamidine can be used in combination.

[0050] As Z in the chemical formula (III), it is not particularly limited and can be appropriately selected according to the purpose. For example, metals such as lead, indium, antimony, tin, copper and bismuth are listed. They can be used alone or in combination of two or more. Among them, lead is particularly preferred, and lead and tin are particularly preferred in combination. In addition, the perovskite layer preferably has a layered perovskite structure, which is shown as a layer composed of a metal halide and a layer arranged with organic cation molecules alternately stacked. The perovskite layer may contain an alkali metal. When the perovskite layer contains at least an alkali metal, it is beneficial to increase the output. As an alkali metal, for example, cesium, rubidium, potassium, etc. are listed. Among these, cesium is preferred.

[0051] As described above, the photoelectric conversion layer 14 may be a perovskite layer formed of a perovskite compound. The method for forming such a perovskite layer is not particularly limited and may be appropriately selected according to the purpose, for example, a method of applying a solution in which a metal halide and a haloalkylamine are dissolved or dispersed and then drying the solution.

[0052] In addition, as a method for forming a perovskite layer, for example, a two-step precipitation method is listed. The two-step precipitation method is a method of forming a perovskite compound by applying a solution in which a metal halide is dissolved or dispersed, drying it, and then immersing it in a solution in which a haloalkylamine is dissolved.

[0053] In addition, other methods for forming a perovskite layer include, for example, a method of applying a solution in which a metal halide and a haloalkylamine are dissolved or dispersed, and adding a weak solvent (solvent with low solubility) for the perovskite compound to precipitate crystals.

[0054] In addition, as another method for forming the perovskite layer, for example, there is a method of vapor-depositing a metal halide in a gas filled with methylamine or the like.

[0055] As a method for forming a perovskite layer, it is particularly preferred to apply a solution in which a metal halide or a haloalkylamine is dissolved or dispersed, and add a weak solvent for the perovskite compound to precipitate crystals. There is no particular restriction on the method for applying these solutions, and it can be appropriately selected according to the purpose, for example, immersion method, spin coating method, spray coating method, infiltration method, roller coating method, air knife method, etc. are listed. In addition, as a method for applying the solution, it can be a method for precipitating it in a supercritical fluid such as carbon dioxide. As a method for adding the above-mentioned weak solvent to precipitate crystals, the weak solvent used can be listed as: hydrocarbons such as n-hexane and n-octane, alcohols such as methanol, ethanol, and 2-propanol, ethers such as diethyl ether and diisopropyl ether, ketones such as acetone and methyl isobutyl ketone, esters such as ethyl acetate, isobutyl acetate, and γ-butyrolactone, nitriles such as acetonitrile and 3-methoxypropionitrile, aromatic hydrocarbon compounds such as benzene, toluene, and chlorobenzene, halogen solvents such as dichloromethane and chloroform, and fluorine solvents such as chlorofluorocarbons, hydrochlorofluorocarbons, and hydrofluorocarbons.

[0056] The thickness of the photoelectric conversion layer 14 (eg, a light absorbing layer, such as a perovskite layer) is not particularly limited, but is preferably 50 to 1200 nm, more preferably 200 to 1000 nm, from the viewpoint of further suppressing performance degradation due to defects or peeling.

[0057] [Electron transport layer] The material used for the electron transport layer 15 is not particularly limited and can be appropriately selected according to the purpose, but a semiconductor material is preferred. The semiconductor material is not particularly limited and known materials can be used, for example, monomer semiconductors, compound semiconductors, organic n-type semiconductors, etc.

[0058] The single semiconductor is not particularly limited, and examples thereof include silicon and germanium.

[0059] The compound semiconductor is not particularly limited, and examples thereof include metal chalcogenides, specifically oxides of titanium, tin, zinc, iron, tungsten, zirconium, hafnium, strontium, indium, cerium, yttrium, lanthanum, vanadium, niobium, and tantalum; sulfides of cadmium, zinc, lead, silver, antimony, and bismuth; selenides of cadmium and lead; and tellurides of cadmium. Other compound semiconductors include phosphides of zinc, gallium, indium, and cadmium, gallium arsenide, copper-indium-selenide, and copper-indium-sulfide.

[0060] The organic n-type semiconductor is not particularly limited, but examples thereof include perylenetetracarboxylic anhydride, perylenetetracarboxylic acid diimide compounds, naphthalene diimide-dithiophene copolymers, benzodiimidazole benzophenanthroline copolymers, C 60 , C 70 、PCBM([6,6]-phenyl-C 61 -butyric acid methyl ester), fullerene compounds such as carbonyl-bridged bithiazole compounds, ALq3 (tris(8-hydroxyquinoline)aluminum), triphenylene bipyridine compounds, silyl heterocyclopentadiene compounds, and oxadiazole compounds.

[0061] Among the above-mentioned materials for the electron transport layer 15, organic n-type semiconductors are particularly preferred.

[0062] The material for forming the electron transport layer 15 may be used alone or in combination of two or more. The crystal type of the semiconductor material is not particularly limited and may be appropriately selected according to the purpose, and may be single crystal, polycrystalline or amorphous.

[0063] The film thickness of the electron transport layer 15 is not particularly limited and may be appropriately selected depending on the intended purpose, but is preferably 5 nm to 1000 nm, more preferably 10 nm to 700 nm.

[0064] There is no particular limitation on the method for forming the electron transport layer 15, and it can be appropriately selected according to the purpose. For example, there are: a method of forming a thin film in a vacuum (vacuum film forming method), a wet film forming method, etc. As a vacuum film forming method, for example, there are: sputtering, pulsed laser deposition (PLD), ion beam sputtering, ion assisted method, ion plating, vacuum evaporation, atomic layer deposition (ALD method), chemical vapor deposition (CVD method), etc. As a wet film forming method, there are: a method of forming by coating a solvent in which an electron transport material is dissolved, and a method of using a sol-gel method in the case of an oxide semiconductor. The sol-gel method refers to a method of making a gel from a solution through chemical reactions such as hydrolysis and polymerization / condensation, and then promoting the densification of the gel by heat treatment. When the sol-gel method is used, the coating method of the sol solution is not particularly limited and can be appropriately selected according to the purpose. For example, the coating method includes: immersion method, spray method, wire rod method, spin coating method, roller coating method, air knife method, gravure coating method, and wet printing method includes: relief printing, offset printing, gravure printing, gravure printing, rubber printing, and screen printing. In addition, the temperature of the heat treatment after the sol solution is applied is preferably 80° C. or more, and more preferably 100° C. or more.

[0065] After the electron transport layer 15 is formed, an electron injection layer (hole blocking layer) may be formed between the electron transport layer 15 and the second electrode 16. As a material for the electron injection layer, BCP (bathocuproine) may be cited, and cesium may be doped. The electron injection layer is preferably 1 to 100 nm, more preferably 3 to 20 nm.

[0066] A passivation layer may be formed between the photoelectric conversion layer 14 and the second electrode 16 (preferably between the photoelectric conversion layer 14 and the electron transport layer 15 , and more preferably between the photoelectric conversion layer 14 and the electron injection layer). The passivation layer is also preferably formed in direct contact with the photoelectric conversion layer 14 and / or the electron injection layer. The passivation layer may consist of only organic matter, only inorganic matter, or both. As the above-mentioned organic matter, for example, there are listed: P1 NH2"R P1 CONH2"2HN-R P2 -NH2", "R P1 CONH-R P2 -NHCOR P1 ”, “R P1 NHCO-R P2 -CONHR P1 ”, “R P1 CONH-R P2 -N(R P1)2" (these are collectively referred to as organic substances for passivation layer). In the above, R P1 Each independently represents a monovalent substituent (preferably an organic group, preferably a hydrocarbon group, more preferably a hydrocarbon group having 1 to 10 carbon atoms), R P2 Each independently represents a divalent linking group (preferably an organic group, preferably a hydrocarbon group, and more preferably a hydrocarbon group having 1 to 10 carbon atoms). The molecular weight of the organic substance is preferably 40 to 600. In addition, the organic matter can form a salt (acid addition salt or base addition salt) with an acid or a base, and the organic matter can also be a passivation layer organic matter and an acid or a base to form a salt. As an acid to form an acid addition salt and a base to form a base addition salt, for example, the acid or base used when the compound represented by chemical formula (I) or (II) forms a salt is listed. Specific examples of the organic substance include ethylenediamine, 2-phenylethylamine, and acid addition salts thereof (hydroiodide, etc.). The organic substance may be used alone or in combination of two or more. Examples of the inorganic substance include metal oxides and metal oxynitrides, such as silicon oxide, silicon nitride, aluminum oxide, silicon oxynitride, molybdenum oxide, and hafnium oxide. The inorganic substance may be used alone or in combination of two or more. The passivation layer preferably contains the organic substance, and the content of the organic substance is preferably 30 to 100 mass %, more preferably 90 to 100 mass %, and further preferably 98 to 100 mass % relative to the total mass of the passivation layer.

[0067] [Second electrode] The second electrode 16 (which may be, for example, a back electrode) is, for example, a layer having a function of extracting electrons from the photoelectric conversion layer 14 via an electron transport layer. In addition, the second electrode 16 is, for example, a layer that functions as an anode (negative electrode).

[0068] The second electrode 16 can be formed directly on the electron transport layer (also called the electron injection layer) 15. In addition, the material of the second electrode 16 is not particularly limited, for example, the same material as the first electrode 12 can be used. As the second electrode 16, there is no particular limitation on its shape, structure and size, and it can be appropriately selected according to the purpose. As the material of the second electrode 16, metals, carbon compounds, conductive metal oxides, conductive polymers, etc. are listed.

[0069] Examples of the metal include platinum, gold, silver, copper, and aluminum.

[0070] Examples of the carbon compound include graphite, fullerene, carbon nanotube, and graphene.

[0071] Examples of the conductive metal oxide include ITO, FTO, and ATO.

[0072] Examples of the conductive polymer include polythiophene and polyaniline.

[0073] The material for forming the second electrode 16 may be used alone or in combination of two or more.

[0074] The second electrode 16 can be formed on the electron transport layer 15 by appropriately using a method such as coating, lamination, vacuum deposition, CVD, or bonding, depending on the type of material used and the type of the hole transport layer 13 .

[0075] In addition, in the photoelectric conversion unit 10 of the present embodiment, at least one of the first electrode 12 and the second electrode 16 is preferably substantially transparent. When the photoelectric conversion unit 10 of the present embodiment is used, it is preferred to make the electrode transparent and allow incident light to enter from the electrode side. In this case, the back electrode (the electrode on the opposite side of the transparent electrode, such as the second electrode 16) is preferably made of a material that reflects light, preferably glass, plastic, or a metal film on which a metal or a conductive oxide is evaporated. In addition, it is also an effective means to provide an anti-reflection layer on the electrode on the incident light side.

[0076] It should be noted that the structure of the photoelectric conversion unit 10 is not limited to Figure 1 For example, the support 11 can be arranged on the Figure 1 The opposite side ( Figure 1 The upper side of the second electrode 16 in the support 11) and the second electrode 16, the electron transport layer 15, the photoelectric conversion layer 14, the hole transport layer 13 and the first electrode 12 may be stacked on the support 11 in this order. In addition, for example, as described above, other structural elements may or may not exist between the layers of the support 11, the first electrode 12, the hole transport layer 13, the photoelectric conversion layer 14, the electron transport layer 15 and the second electrode 16. In addition, although the example in which the first electrode 12 is a transparent electrode and the second electrode 16 is a back electrode is described, the photoelectric conversion unit 10 is not limited thereto. For example, in the photoelectric conversion unit 10, the first electrode 12 may be the back electrode and the second electrode 16 may be the transparent electrode.

[0077] [Package] In order to protect the device (photoelectric conversion unit 10 of this embodiment) from water and oxygen, the photoelectric conversion unit 10 of this embodiment (e.g., solar cell) is preferably encapsulated. The structure of the encapsulation is not particularly limited, and for example, it can be the same as that of a general photoelectric conversion unit (e.g., solar cell). Specifically, for example, the encapsulation material can be applied only to the periphery of the photoelectric conversion unit 10 of this embodiment and covered with glass or a film, or the encapsulation material can be applied to the entire surface of the photoelectric conversion unit 10 of this embodiment and covered with glass or a film, or only the encapsulation material can be applied to the entire surface of the photoelectric conversion unit 10 of this embodiment.

[0078] The material of the sealing member is not particularly limited and may be appropriately selected depending on the intended purpose. For example, epoxy resin or acrylic resin is preferably used and cured, but it may not be cured or only part of it may be cured.

[0079] The epoxy resin is not particularly limited, for example, it is listed as: water dispersion system, solvent-free system, solid system, heat curing type, curing agent mixed type, ultraviolet curing type, etc.; among these, heat curing type and ultraviolet curing type are preferred, and ultraviolet curing type is more preferred. It should be noted that even in the ultraviolet curing type, heating can be performed, and it is preferably heated after ultraviolet curing. As specific examples of epoxy resins, bisphenol A type, bisphenol F type, novolac type, cyclic aliphatic type, long-chain aliphatic type, glycidylamine type, glycidyl ether type, glycidyl ester type, etc. are listed; they can be used alone or in combination of two or more. In addition, as needed, it is preferred to mix the curing agent and various additives into the epoxy resin. In this embodiment, an epoxy resin composition that is already commercially available can be used. Among them, there are also epoxy resin compositions developed and commercially available for use in solar cells or organic EL units, which can be particularly effectively used in this embodiment. Examples of commercially available epoxy resin compositions include TB3118, TB3114, TB3124, and TB3125F (manufactured by ThreeBond Co., Ltd.); WorldRock5910, WorldRock5920, and WorldRock8723 (manufactured by Kyoritsu Chemical Industry Co., Ltd.); and WB90US(P) and WB90US-HV (manufactured by Moresco Co., Ltd.).

[0080] The acrylic resin is not particularly limited, and for example, commercially available acrylic resins developed for solar cells or organic EL units can be effectively used. Examples of commercially available acrylic resin compositions include TB3035B and TB3035C (manufactured by ThreeBond Co., Ltd.).

[0081] As the curing agent, although there is no particular limitation and it can be appropriately selected according to the purpose, for example, amine-based, acid anhydride-based, polyamide-based, other curing agents, etc. are listed. As amine-based curing agents, aliphatic polyamines such as diethylenetriamine and triethylenetetramine, aromatic polyamines such as m-phenylenediamine, diaminodiphenylmethane, and diaminodiphenyl sulfone are listed; as acid anhydride-based curing agents, phthalic anhydride, tetrahydrophthalic anhydride and hexahydrophthalic anhydride, methyltetrahydrophthalic anhydride, methylnadic anhydride, pyromellitic anhydride, chlorobridged anhydride, dodecenyl succinic anhydride, etc. are listed. As other curing agents, imidazoles, polythiol, etc. are listed. These can be used alone or in combination of two or more.

[0082] As the additive, there is no particular limitation, and it can be appropriately selected according to the purpose, for example, filler (filler), interstitial agent, polymerization initiator, desiccant (hygroscopic agent), curing accelerator, coupling agent, softener, colorant, flame retardant, antioxidant, organic solvent, etc. are listed. Among these, filler, interstitial agent, curing accelerator, polymerization initiator, desiccant (hygroscopic agent) are preferred, and filler and polymerization initiator are more preferred. By containing filler as an additive, the infiltration of moisture and oxygen can be suppressed, and the following effects can be further obtained: the volume shrinkage during curing is reduced, the exhaust volume during curing or heating is reduced, the mechanical strength is improved, and the thermal conductivity and fluidity are controlled. Therefore, containing filler as an additive is very effective for maintaining stable output under various environments.

[0083] In addition, regarding the output characteristics and durability of the photoelectric conversion unit, not only the influence of the infiltrated moisture and oxygen cannot be ignored, but also the influence of the exhaust gas generated by the packaging components during curing or heating cannot be ignored. In particular, the exhaust gas generated during heating has a great influence on the output characteristics during storage in a high-temperature environment. By including fillers, gap agents and desiccants in the packaging components, in addition to these themselves being able to inhibit the infiltration of moisture and oxygen, the amount of packaging components used can also be reduced, thereby achieving the effect of reducing exhaust gas. Including fillers, gap agents and desiccants in the packaging components is effective not only during curing, but also when the photoelectric conversion unit is stored in a high-temperature environment.

[0084] The filler is not particularly limited and can be appropriately selected according to the purpose. For example, crystalline or amorphous silica, silicate minerals such as talc, inorganic fillers such as alumina, aluminum nitride, silicon nitride, calcium silicate, and calcium carbonate are listed. Among these, hydrotalcite is particularly preferred. In addition, these can be used alone or in combination of two or more.

[0085] The average primary particle size of the filler is not particularly limited, but is preferably 0.1 μm to 10 μm, more preferably 1 μm to 5 μm. When the average primary particle size of the filler is within the above preferred range, the effect of suppressing the intrusion of moisture and oxygen can be fully obtained, so that the viscosity becomes appropriate, the adhesion to the substrate and the defoaming property are improved, and it is also effective for the width control and processability of the packaging part.

[0086] Relative to the entire packaging component (100 parts by mass), the content of the filler is preferably 10 parts by mass or more and 90 parts by mass or less, and more preferably 20 parts by mass or more and 70 parts by mass or less. By the content of the filler being within the above preferred range, the effect of suppressing the penetration of moisture and oxygen is fully obtained, so that the viscosity also becomes appropriate, and the close adhesion and processability become good.

[0087] The gap agent is also called a gap control agent or a spacer. By containing a gap material as an additive, the gap of the encapsulation part can be controlled. For example, when a packaging component is added to the first substrate or the first electrode and the second substrate is placed thereon for packaging, the gap of the encapsulation part is consistent with the size of the gap agent by mixing the packaging component with the gap agent, so the gap of the encapsulation part can be easily controlled.

[0088] Although there is no particular limitation on the interstitial agent, for example, a granular interstitial agent with uniform particle size, high solvent resistance and heat resistance is preferred, and can be appropriately selected according to the purpose. As the interstitial agent, an interstitial agent with high affinity for epoxy resin and spherical particle shape is preferred. Specifically, glass beads, silica particles, organic resin particles, etc. are preferred. These can be used alone or in combination of two or more. Although the particle size of the interstitial agent can be selected in accordance with the gap of the packaging portion to be set, it is preferably between 1 μm and 100 μm, and more preferably between 5 μm and 50 μm.

[0089] As the polymerization initiator, there is no particular limitation, for example, a polymerization initiator that uses heat or light to initiate polymerization is listed, and it can be appropriately selected according to the purpose, for example, a thermal polymerization initiator, a photopolymerization initiator, etc. are listed. The thermal polymerization initiator is a compound of active substances that generate free radicals and cations by heating, and examples include: azo compounds such as azobisisobutyronitrile (AIBN) and peroxides such as benzoyl peroxide (BPO), etc. As thermal cationic polymerization initiators, benzene sulfonates and alkyl sulfonium salts are used. In the case of epoxy resin, the photopolymerization initiator preferably uses a photocationic polymerization initiator. When the photocationic polymerization initiator is mixed with the epoxy resin and irradiated with light, the photocationic polymerization initiator decomposes and generates an acid, which causes the polymerization of the epoxy resin, thereby performing a curing reaction. The photocationic polymerization initiator has the effects of small volume shrinkage during curing, no interference from oxygen, and high storage stability.

[0090] As the photocationic polymerization initiator, there are listed: aromatic diazonium salts, aromatic iodonium salts, aromatic sulfonium salts, metallocene compounds, silanol-aluminum complexes, etc. In addition, as a polymerization initiator, a photoacid generator having a function of generating acid by light irradiation can also be used. The photoacid generator acts as an acid that initiates cationic polymerization, and there are listed: ionic onium salts such as sulfonium salts and iodonium salts composed of a cationic part and an anionic part. These can be used alone or in combination of two or more.

[0091] The amount of the polymerization initiator added is not particularly limited and may vary depending on the material used, but is preferably 0.5 to 10 parts by mass, more preferably 1 to 5 parts by mass, relative to the entire packaging component (100 parts by mass). By adding an amount within the preferred range, curing can be properly performed, and the residue of uncured material can be reduced, and excessive exhaust can be prevented.

[0092] The desiccant (also referred to as a desiccant) is a material having the function of physically or chemically adsorbing and absorbing moisture. By making the packaged component contain it, the moisture resistance can be further improved and the influence of exhaust gas can be reduced. As the desiccant, although there is no particular limitation and it can be appropriately selected according to the purpose, it is preferably a granular desiccant, for example, inorganic water-absorbing materials such as calcium oxide, barium oxide, magnesium oxide, magnesium sulfate, sodium sulfate, calcium chloride, silica gel, molecular sieves, and zeolites are listed. Among these, zeolites with large moisture absorption are preferred. These can be used alone or in combination of two or more.

[0093] The curing accelerator (also known as a curing catalyst) is a material that accelerates the curing speed and is mainly used for thermosetting epoxy resins. There is no particular limitation on the curing accelerator, and it can be appropriately selected according to the purpose. For example, tertiary amines or tertiary amine salts such as DBU (1,8-diazabicyclo (5,4,0)-undec-7-ene) and DBN (1,5-diazabicyclo (4,3,0)-non-5-ene) are listed; imidazoles such as 1-cyanoethyl-2-ethyl-4-methylimidazole and 2-ethyl-4-methylimidazole; phosphine or phosphonium salts such as triphenylphosphine, tetraphenylphosphonium tetraphenylborate, etc. These can be used alone or in combination of two or more.

[0094] The coupling agent is not particularly limited, as long as it is a material having the effect of improving the molecular bonding force, and can be appropriately selected according to the purpose, for example, silane coupling agents are listed. Specifically, silane coupling agents such as 3-glycidyloxypropyl trimethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, 3-glycidyloxypropyl methyl dimethoxysilane, 2-(3,4-epoxycyclohexyl)ethyl trimethoxysilane, N-phenyl-γ-aminopropyl trimethoxysilane, N-(2-aminoethyl) 3-aminopropyl methyl dimethoxysilane, N-(2-aminoethyl) 3-aminopropyl methyl trimethoxysilane, 3-aminopropyl triethoxysilane, 3-mercaptopropyl trimethoxysilane, vinyl trimethoxysilane, N-(2-(vinylbenzylamino)ethyl) 3-aminopropyl trimethoxysilane hydrochloride, and 3-methacryloxypropyl trimethoxysilane are listed. These may be used alone or in combination of two or more.

[0095] In this embodiment, for example, a sheet adhesive can be used. The sheet adhesive is obtained by, for example, forming a resin layer on a thin sheet by encapsulating resin in advance, and the thin sheet can use glass and a film with high gas barrier properties. In addition, the sheet adhesive can also be generated only by encapsulating resin. The sheet adhesive can be attached to the encapsulating film. In this case, a structure in which a hollow portion is provided on the sheet constituting the sheet adhesive attached to the encapsulating film can be formed so as to be attached to the device.

[0096] When the encapsulation film is used for encapsulation, it is arranged to be opposite to the support so as to clamp the photoelectric conversion device. As the substrate of the encapsulation film, there is no particular restriction on its shape, structure, size, and type, and it can be appropriately selected according to the purpose. The encapsulation film forms a barrier layer on the surface of the substrate to prevent moisture and oxygen from passing through, and the barrier layer can be formed only on one side of the substrate or on both sides.

[0097] The barrier layer may be composed of a material mainly composed of metal oxides, metals, or a mixture of a polymer and a metal alkoxide. Examples of the metal oxides include aluminum oxide, silicon oxide, and aluminum; examples of the polymers include polyvinyl alcohol, polyvinyl pyrrolidone, and methyl cellulose; and examples of the metal alkoxides include tetraethoxysilane, triisopropoxyaluminum, 3-glycidoxypropyltrimethoxysilane, 3-mercaptopropyltrimethoxysilane, and 3-isocyanatepropyltriethoxysilane.

[0098] The barrier layer may be transparent or opaque. In addition, the barrier layer may be a single layer composed of the above materials or a multilayer structure. The barrier layer may be formed by a known method, such as vacuum film forming such as sputtering, immersion method, roller coating, screen printing, spray coating, gravure printing and other coating methods.

[0099] [wiring] In order to efficiently extract the current generated by light, the photoelectric conversion unit 10 (e.g., solar cell) of this embodiment preferably connects the lead (wiring) to the first electrode 12 and the back electrode of the second electrode. The lead is connected to the first electrode and the second electrode using, for example, a conductive material such as solder, silver paste, or graphite. The conductive material can be used alone, or two or more can be mixed, or a multilayer structure can be used. In addition, from the perspective of physical protection, the part where the lead is installed can be covered with an acrylic resin or an epoxy resin.

[0100] Lead wire is a general term for electric wires used to electrically connect power supplies and electronic components in a circuit, and examples thereof include plastic wires and enameled wires.

[0101] The photoelectric conversion unit 10 described above is excellent in photoelectric conversion characteristics and achieves an effect of improved durability.

[0102] [application] The purpose and method of use of the photoelectric conversion unit 10 of this embodiment are not particularly limited. For example, it can be widely used for the same purpose as a general photoelectric conversion unit (for example, a general solar cell). The photoelectric conversion unit (for example, a solar cell) of this embodiment can be applied to a power supply device by combining it with a circuit board that controls the generated current, for example. As the type of equipment using the power supply device, for example, there are listed: electronic desktop computers and solar-powered radio watches. In addition, the solar cell of this embodiment can be applied as a power supply device to mobile phones, electronic paper, thermometers and hygrometers, etc. In addition, it can also be used as an auxiliary power supply to extend the continuous use time of rechargeable or dry cell battery-type electrical appliances, or by combining it with a secondary battery so that it can be used at night, etc. In addition, it can also be used as an independent power supply that does not require replacement of batteries and power supply wiring. Example

[0103] Hereinafter, examples of the present invention will be described, but the present invention is not limited to the following examples.

[0104] [Example 1] The following steps are performed to produce (manufacture) a solar cell as a photoelectric conversion unit.

[0105] Nickel acetate was dissolved in ethanol (50mM / L), heated and stirred at 60°C for 30 minutes, and allowed to stand at room temperature for 1 hour. Monoethanolamine was added thereto so that the molar ratio to nickel acetate was 1:1, and heated and stirred at 60°C for 15 minutes. Further, ultrasonic treatment was performed at 40°C for 15 minutes, and allowed to stand at room temperature for 24 hours. 1mL of the solution was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25mm square), and a nickel oxide layer was formed on the ITO (first electrode) using a spin coater (4000rpm, 30 seconds), and heat treated at 100°C for 10 minutes. The film thickness of the nickel oxide was 20nm. On the nickel oxide layer, 1 ml of DMF solution dissolved with (A-06) (0.1 mmol / L) was placed on the nickel oxide of an ITO glass substrate (a substrate with a first electrode formed on a glass substrate as a support, 25 mm square), and a monomolecular layer (hole transport layer) was formed on the ITO (first electrode) using a spin coater (3000 rpm, 30 seconds). Next, a solution obtained by dissolving cesium iodide (0.738 g), formamidine iodide (7.512 g), methylamine bromide (0.905 g), lead iodide (23.888 g) and lead bromide (1.022 g) in DMF (40.0 mL) and dimethyl sulfoxide (DMSO, 12.0 mL) was used to form a film on the above substrate using a spin coater. The spin coating speed was 3000 rpm, and chlorobenzene (0.3 mL) was added dropwise after 30 seconds. Then, the film was heated at 150°C for 10 minutes to obtain a perovskite layer (photoelectric conversion layer). 60 (electron transport layer), bathocuproin (BCP, 8nm) (electron injection layer), Ag (100nm) (second electrode) were formed by vacuum evaporation to produce a photoelectric conversion unit. After production, the solar cell characteristics of the 25mm square photoelectric conversion unit were evaluated. Its performance is shown in Table 1. In addition, a 500h continuous irradiation test was performed using SunTest XLS+. As a light continuous irradiation test, the light intensity of SunTest XLS+ was adjusted to AM1.5G, 100mW / cm 2 Table 1 also shows the conversion efficiency retention rates measured before and after the test.

[0106] The photoelectric conversion characteristics of the photoelectric conversion unit produced in Example 1 were measured by the method based on the output measurement method of silicon crystal solar cell unit in JIS C8913: 1998. A solar simulator (SMO-250III, manufactured by Spectrometer Co., Ltd.) was equipped with an air mass filter equivalent to AM1.5G, and the light intensity of the solar simulator was adjusted to 100mW / cm using a secondary standard Si solar cell. 2A test sample of the perovskite solar cell unit (the photoelectric conversion unit produced in Example 1) was irradiated with light as a measurement light source, and a source meter (Model 2400 Universal Source Meter, manufactured by Keithley Instruments Inc.) was used to measure the IV characteristic curve. The short-circuit current (Isc), open-circuit voltage (Voc), and fill factor (FF) were obtained from the IV characteristic curve, and then the short-circuit current density (Jsc) and the photoelectric conversion efficiency (PCE) were calculated.

[0107] Formula 1: Short-circuit current density (Jsc; mA / cm 2 )=Isc(mA) / effective light receiving area S(cm 2 ) Formula 2: Photoelectric conversion efficiency (PCE; %) = Voc (V) × Jsc (mA / cm 2 )×FF×100 / 100(mW / cm 2 )

[0108] [Example 2] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution in which (A-06) (0.1 mmol / L) and phosphonobutyric acid (12 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0109] [Example 3] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution in which (A-06) (0.1 mmol / L) and phosphonobutyric acid (6 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0110] [Example 4] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution in which (A-06) (0.1 mmol / L) and phosphonobutyric acid (0.1 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0111] [Example 5] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution in which (A-06) (0.1 mmol / L) and (B-35) (1.0 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0112] [Example 6] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution containing (A-16) (0.1 mmol / L) and terephthalic acid (2.0 mmol / L) was used instead of the DMF solution containing (A-06) (0.1 mmol / L) in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0113] [Example 7] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that a DMF solution containing (A-05) (0.1 mmol / L) and terephthalic acid (2.0 mmol / L) was used instead of the DMF solution containing (A-06) (0.1 mmol / L) in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0114] [Example 8] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, except that nickel copper oxide prepared by the following preparation method was used instead of nickel oxide in Example 1, and further, a DMF solution in which (A-15) (0.1 mmol / L) was dissolved was used instead of a DMF solution in which (A-06) (0.1 mmol / L) was dissolved. The photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below. ·Production method of nickel copper oxide Nickel acetate and copper acetylacetonate (molar ratio of 1:1) were dissolved in 2-methoxyethanol (50mM / L), heated and stirred at 60°C for 30 minutes, and allowed to stand at room temperature for 1 hour. Triethanolamine was added thereto so that the total amount and molar ratio of nickel acetate: copper acetylacetonate was 1:1, and heated and stirred at 60°C for 15 minutes. Further, ultrasonic treatment was performed at 40°C for 15 minutes and allowed to stand at room temperature for 24 hours. 1mL of the solution was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 75mm square), and a nickel copper oxide layer was formed on the ITO (first electrode) using a spin coater (4000rpm, 30 seconds), and heated at 100°C for 10 minutes. The nickel copper oxide film thickness is 18nm.

[0115] [Example 9] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 8, except that a DMF solution in which (A-15) (0.1 mmol / L) and phosphonobutyric acid (6.0 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 8, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0116] [Example 10] Alumina copper prepared by the following preparation method was used instead of nickel oxide in Example 1, and further, a DMF solution containing (A-15) (0.1 mmol / L) was used instead of a DMF solution containing (A-06) (0.1 mmol / L). A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below. ·How to make alumina copper Aluminum acetylacetonate and copper acetylacetonate (molar ratio of 1:1) were dissolved in 2-methoxyethanol (50mM / L), heated and stirred at 60°C for 30 minutes, and allowed to stand at room temperature for 1 hour. Triethanolamine was added thereto so that the total amount and molar ratio of aluminum acetylacetonate: copper acetylacetonate was 1:1, and heated and stirred at 60°C for 15 minutes. Further ultrasonic treatment was performed at 40°C for 15 minutes, and allowed to stand at room temperature for 24 hours. 1mL of the solution was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25mm square), and an aluminum copper oxide layer was formed on the ITO (first electrode) using a spin coater (4000rpm, 30 seconds), and heat treated at 100°C for 10 minutes. The aluminum copper oxide film thickness was 15nm.

[0117] [Example 11] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 8, except that a DMF solution in which (A-15) (0.1 mmol / L) and phosphonobutyric acid (6.0 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 10, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0118] [Example 12] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Embodiment 1, except that a DMF solution in which (A-06) (0.1 mmol / L) and glycine hydrochloride (12.0 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Embodiment 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0119] [Example 13] A DMF solution containing (A-06) (0.1 mmol / L) and 2-aminoethylphosphonic acid (6.0 mmol / L) was used to replace the DMF solution containing (A-06) (0.1 mmol / L) in Example 1, and after forming a hole transport layer, methanol hydrochloride (0.5 mol / L) was added and allowed to stand for 1 minute, and then the excess solution was removed using a spin coater (3000 rpm, 30 seconds). In addition to this operation, a photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, and the photoelectric conversion efficiency was determined. The results of the solar cell characteristics are shown in Table 1 below.

[0120] [Comparative Example 1] A photoelectric conversion unit was produced (manufactured) in the same manner as in Example 1, and the photoelectric conversion efficiency was measured, except that the nickel oxide layer in Example 1 was not provided. The results of the solar cell characteristics are shown in Table 1 below.

[0121] [Comparative Example 2] A photoelectric conversion unit was produced (manufactured) in the same manner as in Example 1, except that a tin oxide layer produced by the following production method was used instead of the nickel oxide layer in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below. Method for making tin oxide layer Ion exchange water was added to the tin oxide colloidal solution (15%, water) to dilute to 1.0%, and the diluted solution was subjected to ultrasonic dispersion for 15 minutes. 1 mL of the solution was placed on an ITO glass substrate (a substrate with a first electrode formed on a glass substrate as a support, 25 mm square), and a tin oxide layer was formed on the ITO (first electrode) using a spin coater (4000 rpm, 30 seconds), and heated at 100°C for 10 minutes. The film thickness of the tin oxide layer was 17 nm.

[0122] [Comparative Example 3] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 3, except that a DMF solution in which (A-06) (0.1 mmol / L) and phosphonobutyric acid (6.0 mmol / L) were dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Comparative Example 2, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below.

[0123] [Comparative Example 4] A photoelectric conversion unit was produced (manufactured) in the same manner as in Example 1, except that a PTAA layer produced by the following production method was used instead of the nickel oxide layer in Example 1, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below. ·How to make PTAA layer 1 mL of a chlorobenzene solution (10 ml) in which PTAA (0.05 g) was dissolved was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25 mm square), and a PTAA layer was formed on the ITO (first electrode) using a spin coater (4000 rpm, 30 seconds), and then heated at 100° C. for 10 minutes. The film thickness of the PTAA layer was 17 nm.

[0124] [Comparative Example 5] A photoelectric conversion unit was produced (manufactured) in the same manner as in Example 1, except that a PEDOT layer produced by the following production method was used instead of the nickel oxide layer in Example 1, and a DMF solution in which (A-15) (0.1 mmol / L) was dissolved was used instead of the DMF solution in which (A-06) (0.1 mmol / L) was dissolved in Example 1. The photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 1 below. ·Method for making PEDOT layer 1 mL of PEDOT:PSS (CLEVIOUS PVPAI 4083) was placed on the ITO of an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25 mm square), and a PEDOT layer was formed on the ITO (first electrode) using a spin coater (5000 rpm, 30 seconds), and heat-treated at 140° C. for 30 minutes. The film thickness of the PEDOT was 24 nm.

[0125] [Table 1]

[0126] According to Table 1, by comparing Example 1 with Comparative Example 1, it is clearly shown that by forming a p-type metal oxide semiconductor layer on the first electrode, high output and high retention after the continuous light irradiation test can be achieved at the same time. By comparing Examples 1 and 2 with Comparative Examples 2 and 3, it is clearly shown that good performance can be achieved by using a p-type metal oxide semiconductor such as the present embodiment instead of an n-type metal oxide semiconductor such as tin oxide by forming the metal oxide on the first electrode. In addition, by comparing Example 1 with Comparative Example 4 and Example 8 with Comparative Example 5, it is clearly shown that good performance can be achieved by using a p-type metal oxide semiconductor of the present embodiment instead of a p-type organic semiconductor by forming the layer on the first electrode. It is clearly shown from these results that the present invention exhibits excellent photoelectric conversion characteristics.

[0127] <Synthesis example 1> (Synthesis of Nickel Oxide Nanoparticles) Nickel nitrate hexahydrate (4.51 mg, 15.5 mmol) and deionized water (15.5 mL) were placed in a long-necked flask and stirred at room temperature for 30 minutes. Then, an aqueous sodium hydroxide solution (10 M) was added dropwise at a rate of 0.5 mL / min while stirring until the pH value was 10. After the addition was completed, stirring was continued for 30 minutes, and the green crystals were separated by a centrifuge (10000 rpm, 10 minutes), the colorless and transparent supernatant was poured out, and then deionized water was added, and the centrifugation was repeated twice. The separated nickel oxide was dried under vacuum at 80°C / 10 hours to obtain a green powder. The powder was ground with a mortar and heated at 270°C for 2 hours to obtain a black nickel oxide powder (1.14 mg, yield 98%).

[0128] (Preparation of Nickel Oxide Dispersion) The nickel oxide powder (1.00 mg) obtained above and deionized water (0.1 mL) were stirred at room temperature for 1 hour, and then ultrasonic waves were applied for 5 minutes to prepare a dispersion. The dispersion was passed through a 0.45 μm PVDF filter, and the particle size was measured by dynamic scattering method using the zeta potential, particle size, and molecular weight measurement system ELSZ-2000 manufactured by Otsuka Electronics. The results are shown in Figure 2 .according to Figure 2 , it can be seen that the average particle size is 2.8nm.

[0129] [Example 14] The following steps are performed to produce (manufacture) a solar cell as a photoelectric conversion unit.

[0130] 100 μL of the nickel oxide dispersion obtained above was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25 mm square), and a nickel oxide layer was formed on the ITO (first electrode) using a spin coater (3000 rpm, 25 seconds), and heat treated at 125° C. for 1 hour. The film thickness of the nickel oxide was 14 nm. On the nickel oxide layer, 100 μL of a DMF solution dissolved with (A-06) (0.1 mmol / L) was placed on an ITO glass substrate (a substrate having a first electrode formed on a glass substrate as a support, 25 mm square), and a monomolecular layer (hole transport layer) was formed on the ITO (first electrode) using a spin coater (3000 rpm, 30 seconds). Then, cesium iodide (0.738g), formamidine iodide (7.512g), methylamine bromide (0.905g), lead iodide (23.888g), and lead bromide (1.022g) were dissolved in DMF (40.0mL) and dimethyl sulfoxide (DMSO, 12.0mL) to form a film on the above substrate using a spin coater. The spin coating speed was 3000rpm, and chlorobenzene (0.3mL) was added dropwise 30 seconds after the start. After that, it was heated at 150°C for 10 minutes to obtain a perovskite layer (photoelectric conversion layer). Then, dihydroiodic acid ethylenediamine (25.5mg) was dissolved in 2-propanol (25mL) and chlorobenzene (25mL) to obtain a solution, and a spin coater (4000rpm, 23 seconds) was used to form a film on the perovskite layer. After that, it was heated at 100°C for 5 minutes to form a passivation layer on the perovskite layer. Then, 20 nm of C 60 (electron transport layer), bathocuproin (BCP8nm) (electron injection layer), Ag (100nm) (second electrode) were formed by vacuum evaporation to produce a photoelectric conversion unit. After production, the solar cell characteristics of the 25mm square photoelectric conversion unit were evaluated. The performance is shown in Table 2. In addition, as a continuous light irradiation test, the light intensity was adjusted to AM1.5G, 100mW / cm 2 The SunTest XLS+ was subjected to a 500-hour continuous irradiation test. The conversion efficiency retention rates measured before and after the test are also shown in Table 2.

[0131] The photoelectric conversion characteristics of the photoelectric conversion unit prepared in Example 14 were measured by a method based on the output measurement method of silicon crystal solar cells in JIS C8913: 1998. A solar simulator (SMO-250III, manufactured by Spectrometer Co., Ltd.) was equipped with an air mass filter equivalent to AM1.5G, and the light intensity of the solar simulator was adjusted to 100 mW / cm using a secondary standard Si solar cell. 2A test sample of the perovskite solar cell unit (the photoelectric conversion unit produced in Example 14) was irradiated with light as a measurement light source, and a source meter (Model 2400 Universal Source Meter, manufactured by Keithley Instruments Inc.) was used to measure the IV characteristic curve. The short-circuit current (Isc), open-circuit voltage (Voc), and fill factor (FF) were obtained from the IV characteristic curve measurement, and then the short-circuit current density (Jsc) and the photoelectric conversion efficiency (PCE) were calculated.

[0132] Formula 1: Short-circuit current density (Jsc; mA / cm 2 )=Isc(mA) / effective light receiving area S(cm 2 ) Formula 2: Photoelectric conversion efficiency (PCE; %) = Voc (V) × Jsc (mA / cm 2 )×FF×100 / 100(mW / cm 2 )

[0133] [Example 15] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the film formation of ethylenediamine dihydroiodate (EDAI2) by spin coating was changed to film formation by vacuum evaporation (film thickness 0.5 nm). The results of the solar cell characteristics are shown in Table 2 below.

[0134] [Example 16] In Example 14, the solution of EDAI2 (25.5 mg) dissolved in 2-propanol (25 mL) and chlorobenzene (25 mL) was changed to a solution of phenylethylamine hydroiodide (PEAI) (20.1 mg) dissolved in 2-propanol (25 mL). In addition, a photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 2 below.

[0135] [Example 17] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the DMF solution in which (A-06) (0.1 mmol / L) was dissolved was changed to a DMF solution in which (A-06) (0.1 mmol / L) and 4-phosphonobutyric acid (0.3 mmol / L) were dissolved. The results of the solar cell characteristics are shown in Table 2 below.

[0136] [Example 18] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the DMF solution in which (A-06) (0.1 mmol / L) was dissolved was changed to a DMF solution in which (A-06) (0.1 mmol / L) and 4-phosphonobutyric acid (1.0 mmol / L) were dissolved. The results of the solar cell characteristics are shown in Table 2 below.

[0137] [Example 19] A photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 1, and the photoelectric conversion efficiency was measured, except that a film formed by dissolving EDAI2 (25.5 mg) in 2-propanol (25 mL) and chlorobenzene (25 mL) in Example 14 was not formed. The results of the solar cell characteristics are shown in Table 2 below.

[0138] [Example 20] A photoelectric conversion unit was produced (manufactured) in the same manner as in Example 14 except that Ag (100 nm) (second electrode) was changed to Cu (100 nm), and the photoelectric conversion efficiency was measured. The results of the solar cell characteristics are shown in Table 2 below.

[0139] [Example 21] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the DMF solution in which (A-06) (0.1 mmol / L) was dissolved was changed to a DMF solution in which (A-15) (0.1 mmol / L) was dissolved. The results of the solar cell characteristics are shown in Table 2 below.

[0140] [Example 22] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the DMF solution in which (A-06) (0.1 mmol / L) was dissolved was changed to a DMF solution in which (A-15) (0.1 mmol / L) and phosphonobutyric acid (0.3 mmol / L) were dissolved. The results of the solar cell characteristics are shown in Table 2 below.

[0141] [Example 23] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the black nickel oxide powder obtained by heating at 270°C for 2 hours after grinding with a mortar in Synthesis Example 1 was changed to a black nickel oxide powder (average particle size of 1.6 nm) obtained by heating at 200°C for 8 hours. The results of the solar cell characteristics are shown in Table 2 below.

[0142] [Example 24] The photoelectric conversion unit was prepared (manufactured) in the same manner as in Example 14, and the photoelectric conversion efficiency was measured, except that the black nickel oxide powder obtained by grinding with a mortar and heating at 270°C for 2 hours in Synthesis Example 1 was changed to a black nickel oxide powder (average particle size 4.1 nm) obtained by heating at 240°C for 8 hours. The results of the solar cell characteristics are shown in Table 2 below.

[0143] [Table 2]

[0144] As described above, according to this example, it was confirmed that good solar cell characteristics and good durability can be obtained by using the hole transport material in the above embodiment for the hole transport layer.

[0145] The present invention has been described above using the embodiments and examples. However, the present invention is not limited to the embodiments and examples described above, and any and appropriate combinations, changes or selections may be made as needed without departing from the gist of the present invention. Industrial Applicability

[0146] As described above, the photoelectric conversion unit of the present invention can be useful as, for example, a solar cell. The purpose and method of use of the photoelectric conversion unit of the present invention are not particularly limited, and can be applied to a wide range of fields by using the same purpose and method as a general photoelectric conversion unit (e.g., a general solar cell). Description of Reference Numerals

[0147] 10: photoelectric conversion unit; 11: support; 12: first electrode; 13: hole transport layer; 13-1: p-type metal oxide semiconductor layer; 13-2: hole transport material layer; 14: photoelectric conversion layer; 15: electron transport layer; 16: second electrode.

Claims

1. A photoelectric conversion unit, characterized in that: The first electrode, the hole transport layer, the photoelectric conversion layer, the electron transport layer and the second electrode are stacked in this order. The photoelectric conversion layer comprises a perovskite compound, The hole transport layer includes a p-type metal oxide semiconductor layer and a hole transport material layer, the p-type metal oxide semiconductor layer is stacked on the main surface of the first electrode on the side of the photoelectric conversion layer, and the hole transport material layer is stacked on the main surface of the p-type metal oxide semiconductor layer on the side of the photoelectric conversion layer, and contains a compound represented by the following chemical formula (I): Ar 1 -(L 1 -X 1 )n...(I) In the chemical formula (I), Ar 1 It is a structure containing an aromatic ring, and the atoms constituting the aromatic ring may or may not contain heteroatoms, Ar 1 With or without -L 1 -X 1 Substituents other than -L 1 -X 1 The structures represented are the same or different from each other, L 1 is bonded to Ar 1 and X 1 A divalent connecting group or a single bond, X 1 It is a group that can chemically bond or hydrogen bond with the p-type metal oxide semiconductor.

2. The photoelectric conversion unit according to claim 1, characterized in that The hole transport material layer comprises a compound represented by the following chemical formula (II), HAS 1 -L 2 -X 2 ...(II) A 1 is an atomic group containing one or more substituents or structures selected from the group consisting of alkoxy, hydroxy, carboxyl, dihydroxyphosphonyl, dialkylphosphonyl, hydroxysulfonyl, amino, monoalkylamino, dialkylamino, monoarylamino, diarylamino, monoalkylaminocarbonyl, dialkylaminocarbonyl, alkylcarbonyloxy, alkoxycarbonyl, aminocarbonyl, aminocarbonylamino, alkylcarbonylamino, alkylsulfonylamino, aminosulfonyl, and nitrogen-containing heterocyclic groups, L 2 Is bond A 1 With X 2 A divalent connecting group or a single bond, X 2 The group is capable of chemically bonding or hydrogen bonding with the first electrode.

3. The photoelectric conversion unit according to claim 1 or 2, characterized in that: The compound represented by the chemical formula (I) forms a monomolecular layer.

4. The photoelectric conversion unit according to claim 2, characterized in that: The molar ratio of the compound represented by the chemical formula (II) to the compound represented by the chemical formula (I) is 1:100 to 1:

1.

5. The photoelectric conversion unit according to claim 1 or 2, characterized in that: X in the chemical formula (I) 1 They are respectively selected from: dihydroxyphosphonyl -P=O(OH)2, carboxyl -COOH, sulfonyl -SO3H, boric acid -B(OH)2, trihalosilyl -SiX3, trialkoxysilyl -Si(OR)3, trihydroxysilyl, dialkylphosphonyl, wherein X is a halogen group and R is an alkyl group.

6. The photoelectric conversion unit according to claim 2, characterized in that: X in the chemical formula (II) 1 They are respectively selected from: dihydroxyphosphonyl -P=O(OH)2, carboxyl -COOH, sulfonyl -SO3H, boric acid -B(OH)2, trihalosilyl -SiX3, trialkoxysilyl -Si(OR)3, trihydroxysilyl, dialkylphosphonyl, wherein X is a halogen group and R is an alkyl group.

7. The photoelectric conversion unit according to claim 1 or 2, characterized in that: The perovskite compound is an organic-inorganic perovskite compound.

8. The photoelectric conversion unit according to claim 1 or 2, characterized in that: The perovskite compound contains at least one of tin or lead.

9. The photoelectric conversion unit according to claim 7, characterized in that: The organic-inorganic perovskite compound contains at least one of tin or lead.

10. The photoelectric conversion unit according to claim 1, wherein: At least a part of the compounds represented by the chemical formula (I) forms acid addition salts.

11. The photoelectric conversion unit according to claim 2, characterized in that: At least a part of the compounds represented by the chemical formula (II) forms acid addition salts.

12. The photoelectric conversion unit according to claim 1, characterized in that: The p-type metal oxide semiconductor layer is formed of p-type metal oxide semiconductor particles.

13. The photoelectric conversion unit according to claim 12, characterized in that: The diameter of the p-type metal oxide semiconductor particles is 1.0 to 30.0 nm.